"Dig if you will the Picture: Prince's Subversion of Hegemonic Black Masculinity, and the Fallacy of Racial Transcendence". Issue 2 (15th March 2019) - Whiteneir, Kevin Talmer
Abstract: Representations of Blackness are often limited to a narrow selection of archetypes despite the everyday experience of Blackness being immeasurably varied. Its intersectionality with class, gender, sexuality, age, ability, and more is complex and cannot simply be transcended as if it does not shape our choices, our ideologies, and our cognitive frameworks. And Prince, as a Black man, and as an artist, was no stranger to this. Flirting with the demarcated boundaries of everything, including gender and race, Prince presented us with a seemingly endless catalogue of musical and performative works that showcase, not "transcend, " the complexity of Blackness, masculinity, and their cultural intersections. This essay will analyze how Prince challenged racial stereotyping, the false equivalence of this with racial transcendence by looking at Prince's Purple Rain era. In doing so, I push to undermine this interpretation of racial transcendence, articulate how race is in fact inextricable from his artistry, and illustrate how an awareness of this serves to benefit the legibility of Blackness and Black gender dynamics within not only Prince's art, but within Western society.